IMPLEMENTING CORPORATE SOCIAL RESPONSIBILITY FUNDS AT LAMBHUK PETROL STATION: Analysing the fulfilment of government regulation and the concept of sadakah wajibah - Afifah, Maisin; Arifin Abdullah (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This article examines the implementation of Corporate Social Responsibility (CSR) funds at the Lambhuk Gas Station (SPBU Lambhuk Banda Aceh) based on the principle of legal obligation as regulated by Government Regulation Number 47 of 2012. The implementation focuses on CSR funds allocated by SPBU Lambhuk, which constitute a legal obligation for limited liability companies operating in sectors related to or utilising natural resources. This study uses an empirical juridical approach, with data collected through interviews and documentation. It investigates whether the implementation of CRS at SPBU Lambhuk complies with applicable regulations and identifies the factors that hinder or support its execution. SPBU Lambhuk has previously carried out CRS activities, such as providing aid to surrounding communities during disasters, supporting religious activities, and contributing to the construction of worship facilities. However, these activities have not been carried out routinely and lack a well-planned annual work programme. The results show that the implementation of CSR funds at SPBU Lambhuk remains suboptimal. The absence of a consistent work programme, weak documentation, limited understanding of CS responsibilities, and insufficient oversight by relevant parties are key factors hindering the realisation of social responsibility. Therefore, efforts to strengthen accountability, transparency, and human resource empowerment are necessary to ensure that CSR truly functions as sadakah wajibah, fulfilling its role in achieving social justice and community welfare.